2021
DOI: 10.21037/atm-20-4578
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram prediction for the overall survival and cancer-specific survival of patients diagnosed with Merkel cell carcinoma

Abstract: Background: Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine carcinoma of the skin, with a high recurrence rate and a high mortality rate worldwide. The purpose of this article is to construct a nomogram that incorporates significant clinical parameters and predicts the survival of individuals with MCC. Methods:The Surveillance, Epidemiology, and End Results (SEER) database was employed to retrospectively analyze all confirmed MCC cases from 2004 to 2015. The data was collected from 3,688 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…[18] Similarly, this phenomenon was demonstrated in a recent analysis, where PORT was identified as a significant contributor to a nomogram for OS, but not to a nomogram for MCC-related survival, again suggesting possible selection bias. [19] Finally, in an analysis of patients with MCC >65 years old, treatment with PORT was found to be associated with improved OS, but not MCC-specific survival. [20] The discrepancy between MCC-related survival and OS in these studies indicate that selection criteria for PORT could be refined, for instance by taking life expectancy into account.…”
Section: Discussionmentioning
confidence: 96%
“…[18] Similarly, this phenomenon was demonstrated in a recent analysis, where PORT was identified as a significant contributor to a nomogram for OS, but not to a nomogram for MCC-related survival, again suggesting possible selection bias. [19] Finally, in an analysis of patients with MCC >65 years old, treatment with PORT was found to be associated with improved OS, but not MCC-specific survival. [20] The discrepancy between MCC-related survival and OS in these studies indicate that selection criteria for PORT could be refined, for instance by taking life expectancy into account.…”
Section: Discussionmentioning
confidence: 96%
“…Black race did not demonstrate significant association in the multivariable analysis performed by Sridharan et al adjusting for sex, patient age and primary tumor site [ 4 ]. Additionally, prior studies have shown OS to be a suboptimal surrogate for cancer-specific survival for patients with MCC [ 21 , 22 , 23 , 24 ]. Optimal consideration of survival for patients with MCC should be evaluated in the context of factors such as immune status [ 14 ], Merkel cell polyomavirus (MCPyV) status, equivalent definitions of race, and competing causes of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that surgery could not improve outcomes and was not significantly correlated with OS and MSS of MCC patients. 20 , 27 Yan et al compared outcomes of patients undergoing different surgical procedures and reported that different surgical types, including LD, EM ≤1 cm, 1 cm < EM ≤ 2 cm, and EM >2 cm, were not linked with differences in patient prognosis. 19 In the present real‐world clinical study, we observed that surgical resection was associated with improved OS, which is consistent with the results of previous studies regarding the effects of surgery on the outcomes of elderly patients with oral tongue squamous cell carcinoma 21 or pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%